PENGEMBANGAN SCRAPBOOK MATERI KALIMAT PERSUASIF DALAM PELAJARAN BAHASA INDONESIA DI KELAS IV SD NEGERI 56 GRESIK - Endah Yogi Shofiana; Nanang Khoirul Umam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
Abstract Writing activity is a way for someone to express an idea or a way to communicate, indirectly conveying messages in written form. In Indonesian language lessons, it is closely related to material that requires students to be able to write good and correct Indonesian. As is the case with persuasive sentence material in grade IV elementary school, in learning about persuasive sentences students still have difficulty understanding the subject matter presented. The main difficulty factors experienced by students are that they are not used to writing and making persuasive sentences, limited vocabulary so it is still difficult to arrange words into persuasive sentences. So from the existing problems, researchers tried to use scrapbook media assistance in the learning process in the classroom, with the help of scrapbooks being able to attract students' attention and increase learning interest in following the learning process because previously in the learning process they had never used media assistance. Keywords : Writing, Persuasive, Scrapbook